2017
DOI: 10.1016/j.eururo.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Node Procedure in Prostate Cancer: A Systematic Review to Assess Diagnostic Accuracy

Abstract: This literature review showed a high diagnostic accuracy for sentinel node biopsy in detecting positive lymph nodes in prostate cancer, but further studies are needed to explore the effect of sentinel node biopsy on complications and oncologic outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
101
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(110 citation statements)
references
References 43 publications
7
101
1
1
Order By: Relevance
“…Therefore, patients with high risk of nodal involvement should undergo an extended PLND, based on a template including common iliac arteries up to the cross with ureter obturator region and LNs medial and lateral of the internal iliac vessels. As suggested by the authors, SNB in combination with ePLND seems to provide a better nodal removal by increasing the number of affected nodes in 5% of cases in high risk PCa (9).…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Therefore, patients with high risk of nodal involvement should undergo an extended PLND, based on a template including common iliac arteries up to the cross with ureter obturator region and LNs medial and lateral of the internal iliac vessels. As suggested by the authors, SNB in combination with ePLND seems to provide a better nodal removal by increasing the number of affected nodes in 5% of cases in high risk PCa (9).…”
mentioning
confidence: 76%
“…In (9). The authors have identified more than 300 articles and selected 21 studies identified from January 1, 1999 to May 31, 2016, recruiting a total of 2,509 patients.…”
mentioning
confidence: 99%
“…One meta-analysis demonstrated a pooled detection rate of 93.8% for the radio-guided sentinel approach [17]. A systematic literature review considering 21 studies recruiting 2509 patients, found a median cumulative percentage detection rate of 95.9% (IQR 89.4-98.5%) [4]. However, in the SentiMag Pro II study, we adjusted the exclusion criteria according to some of the fundamental limitations of sLND already described by us and others (e.g., previous hormonal treatment or prostate surgery), which may have improved our detection rate [13].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic accuracy of this radioactive sentinel LN dissection (sLND) approach was determined in a systematic literature review. Twenty-one studies including 2509 patients were analyzed [4]. The findings demonstrated that the diagnostic reliability of eLND and sLND were almost comparable.…”
Section: Introductionmentioning
confidence: 96%
“…An enabling technology is the ability to remove lymph nodes with exquisite accuracy and in a minimally invasive manner. In human cancer patients, resection of only the first tumor-draining nodes has become standard of care for breast cancer and an expanding list of tumor types [1517]. The technology involves injection of radioactive colloid around the target tissue which is then carried through the lymphatic vessels to lymph nodes [18].…”
Section: Discussionmentioning
confidence: 99%